Obesity mediates the association between psoriasis and diabetes incidence: a population-based study - Zuojiao Xu; Kaihua Ma; Yinuo Zhai; Jing Wang; Yan Li (Diabetology & Metabolic Syndrome)
Abstract Introduction The aim of this study was to explore the association between psoriasis and diabetes and to assess the potential moderating role of obesity in this relationship. Methods The study involving data from 21,835 NHANES participants during 2003–2006 and 2009–2014. The analysis included body mass index (BMI), as well as information about psoriasis and diabetes obtained from questionnaires. The study employed weighted logistic regression to examine the association between psoriasis and diabetes. The nonlinear relationship between obesity, diabetes, and psoriasis was explored through smooth curve fitting, stratified by age and gender. In addition, the authors conducted mediation analysis, which suggested that obesity partially mediated the association between psoriasis and diabetes prevalence. Results After adjusting for relevant variables, we found that individuals with psoriasis had a significantly higher incidence of diabetes (OR = 1.48, 95% CI = 1.16–1.90, P = 0.002). A positive relationship was identified between BMI levels and diabetes occurrence among individuals with psoriasis, with a significant difference observed between the highest (Q4) and lowest (Q1) BMI quartiles (P < 0.05). Further analysis using smooth curve fitting demonstrated the consistent association between BMI and diabetes, which was also evident in psoriasis patients. Age-stratified analysis showed that diabetes was more prevalent among older adults compared to younger individuals at the same BMI levels. For psoriasis, an inflection point was noted in men where its prevalence began to decline as BMI exceeded a certain threshold. Similarly, in younger adults, psoriasis prevalence decreased above a specific BMI threshold. Additionally, mediation analysis indicated that obesity played a partial role in linking psoriasis and diabetes, accounting for approximately 22.91% of this association. Conclusion The study found an association between psoriasis and diabetes. Additionally, the analysis suggested that obesity may partially contribute to this relationship, indicating it could play a role in linking the two conditions.